2010
DOI: 10.4049/jimmunol.0902245
|View full text |Cite
|
Sign up to set email alerts
|

Lack of TNFR p55 Results in Heightened Expression of IFN-γ and IL-17 during the Development of Reactive Arthritis

Abstract: Reactive arthritis (ReA) is a type of arthritis originating from certain gastrointestinal or genitourinary infections. In previous studies, we reported the development of progressive Yersinia enterocolitica-induced ReA in mice lacking TNFR p55; however, the mechanisms underlying this effect are still uncertain. In this study, we investigated the impact of TNFR p55 deficiency in modulating Ag-specific Th1 and Th17 responses during this arthritogenic process. We found more severe ReA in TNFRp55−/− mice compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 54 publications
8
40
1
1
Order By: Relevance
“…Furthermore, higher concentrations of IL-6 were detected in the joints of these mice which showed a severe chronic synovitis (Eliç abe et al 2010). These results are also consistent with those obtained in other arthritis models (Iwanami et al 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, higher concentrations of IL-6 were detected in the joints of these mice which showed a severe chronic synovitis (Eliç abe et al 2010). These results are also consistent with those obtained in other arthritis models (Iwanami et al 2008).…”
Section: Discussionsupporting
confidence: 81%
“…The role of IL-17 in the pathogenesis of synovitis in RA has been well documented [53]. Additionally, we have previously demonstrated that IL-17 mediates articular inflammation in reactive arthritis [34]. In the present study, we found that the articular IL-17 circadian rhythm was abolished in the KO mice, suggesting a role for TNF in the circadian regulation of IL-17.…”
Section: Discussionsupporting
confidence: 72%
“…Homogenates of ankle joints were obtained as previously described by Eliçabe et al [34]. Mouse IL-17, TNF, IL-6, and IL-10 were quantified in clarified joint homogenates by using capture enzyme-linked immunosorbent assay kits (eBioscience, San Diego, CA, USA) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Our reported findings in mice showed that the increase in Th17 cells observed after anti-TNFα therapy was partly due to increased production of p40 1 2. This was based on observations that TNFα inhibits p40 production in vitro and that blockade of p40 inhibits the expansion of Th17 cells in vivo.…”
Section: Resultsmentioning
confidence: 81%
“…However, we made the unexpected discovery that in collagen-induced arthritis (CIA), treatment with anti-TNFα leads to an increase in pathogenic Th1 and Th17 cells 1. Mechanistically, the increase in Th1 and Th17 cells in TNFR1−/− mice may be attributable in part to increased production of p40, the common subunit of interleukin (IL)-12 and IL-23, cytokines that are important for the differentiation/survival of Th1 and Th17 cells, respectively 1 2…”
Section: Introductionmentioning
confidence: 99%